Screening for traumatic stress in children and adolescents with congenital heart disease. (March 2023) - Konkel, Terri; Kroll, Kristin H.; Goertz, Mackenzie T.; Lavoie, Julie; Bagli, Sravya Patil; Kogutkiewicz, Katie; Kostroski, Robin; Scott, Leslie; Stoll, Patricia; Andres, Jenny; Saudek, David; Handler, Stephanie S.; et al.
Abstract: Background: Previous research has indicated that up to one-third of children undergoing cardiac surgery develop posttraumatic stress disorder (PTSD) following cardiac surgery. Despite the potential long term implications for mental health from this finding, there is no uniform screening procedure for traumatic stress that exists within pediatric cardiac care. Objectives: A quality improvement initiative was developed to improve standards of care to better identify, manage, and prevent traumatic stress in pediatric cardiology patients. Methods: Quality improvement science methodology was utilized to develop, implement, study, and adopt changes in clinical practice within a pediatric cardiac outpatient clinic. Specifically, children who had undergone cardiac surgery, interventional cardiac catheterization, or heart transplant were offered screening for symptoms of traumatic stress using the Children's Revised Impact of Events Scale. Chi-Square tests and logistic regression were used to analyze differences associated with sociodemographic variables, type of surgical repair, and version of the traumatic stress symptom screener that was utilized. Results: Successful implementation to improve quality of care occurred during a 24-month period as screening of eligible patients for traumatic stress increased from 0 % to 95 %. At risk scores for traumatic stress were found in 14 % of patients who were then subsequently referred to social work for further assessment and triage to mental and behavioral health services. Access to education about traumatic stress increased for patients, parents, and the medical team via the use of informational teaching sheets and increased dialogues among staff. Conclusion: A multidisciplinary quality improvement intervention was effective in screening children at risk for traumatic stress who had experienced cardiac surgery, interventional cardiac catheterization, or heart transplant. Administering a screening tool for traumatic stress appears to be an effective means of identifying patients at risk for traumatic stress. Highlights: As many as one-third of children undergoing cardiac surgery develop posttraumatic stress disorder (PTSD) following cardiac surgery Given that there is no uniform screening procedure for traumatic stress that exists within pediatric cardiac care, a quality improvement initiative was developed to develop an outpatient screening protocol to assess for traumatic stress At risk scores for traumatic stress were found in 14 % of pediatric cardiology patients who were then referred to social work for assessment and triage to mental and behavioral health services Administering a screening tool for traumatic stress appears to be an effective means of identifying patients at risk for traumatic stress